For a General Theory of Health: preliminary epistemological and anthropological notes Para uma Teoria Geral da Saúde: anotações epistemológicas e antropológicas preliminares - Naomar de Almeida Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
In order to conduct a preliminary evaluation of the conditions allowing for a General Theory of Health, the author explores two important structural dimensions of the scientific health field: the socio-anthropological dimension and the epistemological dimension. As a preliminary semantic framework, he adopts the following definitions in English and Portuguese for two series of meanings: disease = patologia, disorder = transtorno, illness = enfermidade, sickness = doença, and malady = moléstia. He begins by discussing some sociological theories and biomedical concepts of health-disease, which, despite their limitations, can be used as a point of departure for this undertaking, given the dialectical and multidimensional nature of the disease-illness-sickness complex (DIS). Second, he presents and evaluates some underlying socio-anthropological theories of disease, taking advantage of the opportunity to highlight the semeiologic treatment of health-disease through the theory of "signs, meanings, and health practices". Third, he analyzes several epistemological issues relating to the Health theme, seeking to justify its status as a scientific object. Finally, the author focuses the discussion on a proposal to systematize various health concepts as an initial stage for the theoretical construction of the Collective Health field. Com o objetivo de avaliar preliminarmente as condições de possibilidade de uma Teoria Geral da Saúde, explora-se duas das mais importantes dimensões estruturantes do campo científico da saúde: a dimensão sócio-antropológica e a dimensão epistemológica. Como marcação semântica preliminar, propõe-se uma fixação de sentido em Português para duas séries significantes: disease = patologia, disorder = transtorno, illness = enfermidade, sickness = doença, malady = moléstia. Inicialmente, discute-se algumas teorias sociológicas e concepções biomédicas de saúde-doença que, não obstante suas limitações, sem dúvida poderão ser tomadas como ponto de partida para este esforço, dado o caráter dialético e multidimensional do Complexo D-E-P (doença-enfermidade-patologia). Em segundo lugar, algumas abordagens sócio-antropológicas articuladoras de teorias de doença são apresentadas e avaliadas, aproveitando-se a oportunidade para destacar um tratamento semiológico da saúde-doença, através da teoria dos "signos, significados e práticas de saúde". Em terceiro lugar, analisam-se algumas questões epistemológicas em torno do tema Saúde, buscando justificar o seu estatuto de objeto científico. Finalmente, coloca-se em discussão uma proposta de sistematização de distintos conceitos de saúde, como etapa inicial para a construção teórica do campo da Saúde Coletiva.